Respuesta :
Option C: [tex](x+1)^2+(y+3)^2=20[/tex] is the equation of the circle.
Explanation:
Given that the endpoints of the circle are at (-3,-2) and (1,-4)
The equation of the circle can be determined using the formula,
[tex](x-a)^{2}+(y-b)^{2}=r^{2}[/tex]
where [tex](a, b)[/tex] are the coordinates of the center and r is the radius.
Center:
The center of the circle can be determined using the midpoint formula,
[tex]Center=(\frac{x_1+x_2}{2}, \frac{y_1+y_2}{2} )[/tex]
Substituting the coordinates (-3,-2) and (1,-4) in the above formula, we get,
[tex]Center=(\frac{-3+1}{2}, \frac{-2-4}{2} )[/tex]
[tex]Center=(\frac{-2}{2}, \frac{-6}{2} )[/tex]
[tex]Center=(-1,-3 )[/tex]
Thus, the center of the circle is at (-1,-3)
Radius:
The radius of the circle can be determined using the distance formula,
[tex]r=\sqrt{\left(x_{2}-x_{1}\right)^{2}+\left(y_{2}-y_{1}\right)^{2}}[/tex]
Substituting the coordinates (-3,-2) and (1,-4) in the above formula, we get,
[tex]r=\sqrt{\left(1+3\right)^{2}+\left(-4+2\right)^{2}}[/tex]
[tex]r=\sqrt{\left(4\right)^{2}+\left(-2\right)^{2}}[/tex]
[tex]r=\sqrt{\left16+\left4}[/tex]
[tex]r=\sqrt{20}[/tex]
Thus, the radius of the circle is [tex]\sqrt{20}[/tex]
Equation of the circle:
Substituting the center and the radius of the circle in the equation [tex](x-a)^{2}+(y-b)^{2}=r^{2}[/tex], we get,
[tex](x+1)^2+(y+3)^2=(\sqrt{20} )^2[/tex]
Simplifying, we get,
[tex](x+1)^2+(y+3)^2=20[/tex]
Therefore, the equation of the circle is [tex](x+1)^2+(y+3)^2=20[/tex]
Hence, Option C is the correct answer.